Factors affecting cryptocurrency adoption in digital market of Malaysia - Miraz, Mahadi Hasan (2021)
Cryptocurrency plays an important role in today's digital currency environment. Improving cryptocurrency adoption is important for consumers and practitioners, as it improves understanding, enhances behavior, attitude, trust, and increases satisfaction. Though the lack of cryptocurrency adoption is a significant issue that arises in the digital market, cryptocurrency adoption is crucial to the support of technology capability facilitated with appropriate behavioral intention too. Considering the fact, this study intended to investigate the impact of cryptocurrency adoption in the digital market in Malaysia. This empirical study examined the role of trust (TR), social influence (SI), cryptocurrency transaction transparency (CTT), technology awareness (TA), facilitating conditions (FC), performance expectancy (PE), attitude (AT), customer satisfaction on behavioral intention (BI) and cryptocurrency adoption (CA). The study also intended to examine the role of behavioral intention as a mediator in the context of cryptocurrency adoption. In line with the research objectives, systematic random sampling was used in this study. Cross-sectional data were collected using a questionnaire at the cryptocurrency consumer of Malaysia, which produced a total of 349 usable responses. The study employed Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. Findings o the study revealed that TR, SI, CTT, TA, and FC positively affect CA (dependent variable) through the mediation of behavioral intention (BI) in Malaysia's digital market. On the other hand, PE, AT, and CS negatively affect cryptocurrency adoption in Malaysia's digital market. Future researchers may replicate the study in different countries in a different industry context and integrate similar constructs to broaden the current body of knowledge.